STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH PERTAMA 22 MUARO JAMBI - Desmawati, Dewi; Jamaluddin; Zaspendi, Hamdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the principal’s strategy in improving the quality of education at State Junior High School 22 Muaro Jambi. The background of this research is based on the gap between the expected standards of educators and educational staff and the actual conditions in schools, including the limited number of teachers, uneven competencies, and limited facilities. This research employed a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation involving the principal, teachers, administrative staff, and school committee, and were analyzed using descriptive techniques. The findings indicate that the quality of education in terms of educators and educational staff is generally categorized as good, although it is not yet evenly distributed, particularly in the mastery of technology and the implementation of innovative learning methods. The obstacles faced include limited human resources, high workload, varying levels of competence and motivation, and inadequate facilities and infrastructure. The principal’s strategies include teacher professional development, proportional workload management, motivation enhancement, optimization of educational staff roles, strengthening supervision, and collaboration with parents and the school committee. These findings show that strategic leadership plays a crucial role in improving educational quality in a sustainable manner.